Deregulated JNK signaling enhances apoptosis during hyperthermia - Atsushi Enomoto; Takemichi Fukasawa; Hiroshi Terunuma; Keiichi Nakagawa; Ayumi Yoshizaki; Shinichi Sato; Noriko Hosoya; Kiyoshi Miyagawa (International Journal of Hyperthermia)
Purpose c-Jun N-terminal kinases (JNKs) comprise a subfamily of mitogen-activated protein kinases (MAPKs). The JNK group is known to be activated by a variety of stimuli. However, the molecular mechanism underlying heat-induced JNK activation is largely unknown. The aim of this study was to clarify how JNK activity is stimulated by heat.Methods and materials The expression levels of various MAPK members in HeLa cells, with or without hyperthermia treatment, were evaluated via western blotting. The kinase activity of MAPK members was assessed through in vitro kinase assays. Cell death was assessed in the absence or presence of siRNAs targeting MAPK-related members.Results Hyperthermia decreased the levels of MAP3Ks, such as ASK1 and MLK3 which are JNK kinase kinase members, but not those of the downstream MAP2K/SEK1 and MAPK/JNK. Despite the reduced or transient phosphorylation of ASK1, MLK3, or SEK1, downstream JNK was phosphorylated in a temperature-dependent manner. In vitro kinase assays demonstrated that heat did not directly stimulate SEK1 or JNK. However, the expression levels of DUSP16, a JNK phosphatase, were decreased upon hyperthermia treatment. DUSP16 knockdown enhanced the heat-induced activation of ASK1–SEK1–JNK pathway and apoptosis.Conclusion JNK was activated in a temperature-dependent manner despite reduced or transient phosphorylation of the upstream MAP3K and MAP2K. Hyperthermia-induced degradation of DUSP16 may induce activation of the ASK1–SEK1–JNK pathway and subsequent apoptosis.